MiR-181a Reduces Platelet Activation via the Inhibition of Endogenous RAP1B - Dahiya, Neetu (Microrna, 2020)
AIM: Since RAP1B is critical for platelet functions, including hemostasis, this study was conducted to identify RAP1B regulating microRNAs (miRNAs) in ex vivo stored platelets. BACKGROUND: Previous studies with platelets identified factors affecting RAP1B activity but regulatory miRNAs that affect RAP1B protein expression have not been reported. OBJECTIVE: To understand the functional significance of miRNA mediated regulation of RAP1B in stored platelets, using microRNA, miR-181a as an example. METHODS: A Tagged RNA Affinity approach (MS2-TRAP) was employed to identify miRNAs that bound to the 3` untranslated region (3`UTR) of the RAP1B mRNA in HeLa cells as an assay system. And subsequently, the mRNA 3’UTR:miRNA interactions were verified in platelets through the ectopic expression of miR-181a mimic and appropriate controls. The interaction of such miRNAs with RAP1B mRNA was also validated by qRT-PCR and Western analysis. RESULTS: Sixty-two miRNAs from MS2 assay were then compared with already known 171 platelet abundant miRNAs to identify a common set of miRNAs. This analysis yielded six miRNAs (miR-30e, miR-155, miR-181a, miR-206, miR-208a and miR-454), which are also predicted to target RAP1B mRNA. From this pool, miR-181a was selected for further study since RAP1B harbors two binding sites for miR-181a in its 3′UTR. Ectopic expression of miR-181a mimic in platelets resulted in lowering the endogenous RAP1B at both mRNA and protein levels. Further, miR-181a ectopic expression reduced the surface expression of the platelet activation marker, P-selectin. CONCLUSION: MicroRNA-181a can target RAP1B and this interaction has the potential to regulate platelet activation during storage.